The intricacies of the representation of the local and target cultures in language teaching - Taimur Sabih (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
It can be argued that the English Language Teaching (ELT) content produced locally in Pakistan is heavily influenced by religious and nationalistic concepts tending to overlook the target culture of the English language as well as the culture of the minorities dwelling in Pakistan. Recently, the polarization in the Pakistani society has intensified and religious intolerance is on the rise. Therefore, the objective of this study is to find out the extent to which the content of the textbooks produced in Pakistan plays a role – if any – in the prevalent polarization and intolerance in the Pakistani society. This study explores this phenomenon by analyzing the content of an ELT textbook published in Sindh, Pakistan. It relies on interpretive content analysis coupled with relevance sampling. The research design is composed of three linear steps that include identifying pertinent texts, interpretive content analysis, and finally, inferring the answers to the research question backed up by textual evidence. Relevance sampling helped choose the sample texts pertinent to this study based on the cultural, religious, and nationalistic notions that the texts touched upon. Data were gathered by meticulously reading the sample texts that were rich in vocabulary and historical discourse related to nationalism and religion.The findings reveal that the content of the ELT textbook does not present the learners with any target culture-focused content. It is also noticed that there is a strict focus on religious and nationalistic concepts while the cultures of certain religious minorities and sects do not find any place in the content. The two main identified overarching themes are religiosity and nationalism.